Perencanaan Pembangunan Pariwisata Dalam Rangka Meningkatkan Daya Tarik Wisata Di Kabupaten Kutai Kartanegara (Studi Di Dinas Pariwisata Kabupaten Kutai Kartanegara) - zulfiandri kurniawan (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2017)
This study aims to analyze tourism development planning in order to increase tourist attraction in Kutai Kartanegara district, there are natural, cultural and artificial tourist attractions in Kutai Kartanegara district which are still largely undeveloped. The results showed that tourism development planning in Kutai Kartanegara district carried out by the District Tourism Office of Kutai Kartanegara began with the determination of the objectives and targets set out in the Strategic Plan, then data collection and analysis were carried out in the form of internal and external data. preparation of plans that are finally realized in programs and activities, the planning stages that are carried out are in accordance with tourism development planning through several approaches. Stakeholders involved in tourism development planning, namely the government, the private sector and the community. There are inhibiting factors in tourism development planning in Kutai Kartanegara District, namely human resource planning factors, system factors used and funding factors in tourism planning.Keywords: tourism development planning, tourist attraction